Upaya Meningkatkan Ketrampilan Berbicara Melalui Metode Bercerita Dengan Boneka Tangan Pada Anak Kelompok B Tk Pertiwi Pogung 01 Cawas Klaten Tahun Ajaran 2016/2017 - Retnadewi, Atika, Drs. Haryono Yuwono, M.Pd (2017)
This research aims to know the increase in the speaking skill in the children of Group B TK Pertiwi Pogung 01 Cawas Klaten in the academic year of 2016/2017 through the method of story telling using a hand doll. This research is a class action research [penelitian tindakan kelas (PTK)]. Subjects in this research are the students of Group B of TK Pertiwi Pogung 01 in the academic year of 2016/2017. This research was conducted in two cycles in four times of meeting. The procedure of research includes four stages, they are: action plan, action performance, observation, and reflection. The data of the children's speaking skill and the data of teaching learning process were through the method of storytelling using a hand doll which were collected through the method of observation, interview and documentation. This research used triangulation by finding the data from many data sources. Based on the results of the actions in the cycle I and cycle II which had been conducted, they showed that there is an increasing in the speaking skill in the children of Group B of TK Pertiwi Pogung 01 Cawas Klaten in the academic year of 2016/2017. Before doing the cycles, it obtained the result that the children reached 40.52%, cycle I reached 64.76% and cycle II reached 85.22%. The conclusion from this research is that the method of storytelling using a hand doll can increase the speaking skill in the children of Group B TK Pertiwi Pogung 01 Cawas Klaten in the academic year of 2016/2017. Keywords: speaking skill, method of storytelling with hand doll